Dynamical Analysis of a Pest Management Model with Saturated Growth Rate and State Dependent Impulsive Effects - Wencai Zhao; Tongqian Zhang; Xinzhu Meng; Yang Yang (Abstract and Applied Analysis)
A new pest management mathematical model with saturated growth is proposed. The integrated pest management (IPM) strategy by introducing two state dependent pulses into the model is considered. Firstly, we analyze singular points of the model qualitatively and get the condition for focus point. Secondly, by using geometry theory of impulsive differential equation, the existence and stability of periodic solution of the system are discussed. Lastly, some examples and numerical simulations are given to illustrate our results.